2020
DOI: 10.1177/1557988320970071
|View full text |Cite
|
Sign up to set email alerts
|

SRY-Positive 46, XX Testicular Disorder of Sexual Development With Leydig Cell Tumor

Abstract: The risk of a gonadal tumor is high in testicular disorder of sexual development (DSD) with the Y chromosome, but cases of DSD without the Y chromosome are extremely rare. We reported a gonadal tumor in a phenotypically male individual with 46, XX testicular DSD. A testicular tumor was incidentally found in a 32-year-old phenotypic male who was presented to the hospital with male infertility. A diagnosis of 46, XX testicular DSD was made by the presentation of karyotype analysis of 46, XX with the sex-determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, it is important to note that 46,XX patients without Y chromosome-associated fragments do not have a high risk of developing tumors. Carcavilla et al [ 4 ] reported a case of 46, XX(SRY +) male child with undifferentiated spermatogenic tumor of unknown genitalia and spermatogenic tubule, while Osaka et al [ 5 ] documented a rare case of 46,XX(SRY +) male patient with testicular Leydig cell tumor. The occurrence of this scenario can be attributed to two factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that 46,XX patients without Y chromosome-associated fragments do not have a high risk of developing tumors. Carcavilla et al [ 4 ] reported a case of 46, XX(SRY +) male child with undifferentiated spermatogenic tumor of unknown genitalia and spermatogenic tubule, while Osaka et al [ 5 ] documented a rare case of 46,XX(SRY +) male patient with testicular Leydig cell tumor. The occurrence of this scenario can be attributed to two factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, individuals with 46, XX DSD are caused by a translocation of a segment of the Y chromosome that carries the SRY gene during meiosis [ 3 ]. The presence of the SRY gene may increase the risk of developing gonadal tumors, specifically gonadal germ cell tumors [ 4 ] or testicular Leydig tumors [ 5 ]. However, there have been no reported cases of extragonadal germ cell tumors associated with this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 2 and 3 show FISH analysis in two different cases with SRY negative [ 8 ] and positive [ 9 ] karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Nongerm cell tumors in gonads of patients with DSD are very rare. There are single reports of Leydig cell tumors in 46,XX patients with androgen excess caused by adrenal hyperplasia [ 10 ] and 46,XX DSD, testicular [ 11 ].…”
Section: Discussionmentioning
confidence: 99%